1996
DOI: 10.1136/adc.74.2.164
|View full text |Cite
|
Sign up to set email alerts
|

Comparing efficacy and tolerability of ibuprofen and paracetamol in fever.

Abstract: The purpose of this study was to compare antipyretic activity and evaluate tolerability of ibuprofen and paracetamol suspension in the treatment of febrile children. It was designed as a double blind, parallel group, multiple dose study comparing ibuprofen (20 mg/kg/24 hours) with paracetamol (50 mg/kg/24 hours) given at six hourly intervals for a maximum of 12 doses. Children on paediatric wards between the ages of 0-2 and 12 years, with fever as defined by an axillary temperature ¢ 37 5°C, were included. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
2
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 9 publications
2
91
2
1
Order By: Relevance
“…In the second study, reduction in temperature and improvement in discomfort levels were more or less equal in the two groups. 60 Among the combined treatment trials, we found no study investigating whether there is a relationship between a child's temperature and his or her level of discomfort.…”
Section: Evidence For a Relationship Between Temperature And Discomfortmentioning
confidence: 96%
See 2 more Smart Citations
“…In the second study, reduction in temperature and improvement in discomfort levels were more or less equal in the two groups. 60 Among the combined treatment trials, we found no study investigating whether there is a relationship between a child's temperature and his or her level of discomfort.…”
Section: Evidence For a Relationship Between Temperature And Discomfortmentioning
confidence: 96%
“…Among the studies comparing antipyretic monotherapies, we found two 59,60 in which both temperature and fever-associated symptoms were measured. In the first, 59 although no direct association between temperature and discomfort was described, at 6 hours temperature had fallen to a greater extent and discomfort levels had improved more in the ibuprofen group than in the paracetamol group.…”
Section: Evidence For a Relationship Between Temperature And Discomfortmentioning
confidence: 99%
See 1 more Smart Citation
“…Doses of 10 mg/kg of both drugs were compared in three large studies: one found no difference (7), and in the others, ibuprofen was found to be more effective than APAP (9,11). APAP 12.5 mg/kg has been compared with ibuprofen 5 to 10 mg/kg in three studies (13,14,16). One showed that 8 mg/kg ibuprofen caused greater temperature reduction (13,14), and two demonstrated that ibuprofen 5 mg/kg was not different from APAP 12.5 mg/kg (13,16).…”
Section: Efficacy Studiesmentioning
confidence: 99%
“…APAP 12.5 mg/kg has been compared with ibuprofen 5 to 10 mg/kg in three studies (13,14,16). One showed that 8 mg/kg ibuprofen caused greater temperature reduction (13,14), and two demonstrated that ibuprofen 5 mg/kg was not different from APAP 12.5 mg/kg (13,16). A 1976 study showed that ibuprofen 6 mg/kg was as effective as APAP 12.5 mg/kg (15).…”
Section: Efficacy Studiesmentioning
confidence: 99%